Evaluation of Digital- English Project Based Learning (PJBL) Model through Eye Tracking Analysis in Higher Education - Marlina, Yuli; Yunas, Muhammad Faisal (STAI Miftahul Ula Nganjuk, 2024)
This study uses Eye Tracking technology to analyze students' visual interactions with English learning films. The goal is to actively engage pupils and develop practical skills, not just test conceptual understanding. Eye Tracking is a technique for monitoring students' eye movements and attentiveness while interacting with digital objects. This method seeks to improve learning effectiveness by recognizing patterns of visual interaction in critical areas of the movie. In the digital age, technology plays an important role in shifting the learning paradigm. Project Based Learning (PJBL) is an increasingly popular approach in which students learn through real-world projects. The purpose of this study is to assess students' grasp of English topics using a digital-based PJBL. This study used Eye Tracking analysis to monitor students' eye movements and attentiveness while interacting with digital materials. The data suggests that pupils focus on relevant portions, particularly complex ones like grammar. This emphasizes the significance of focusing on key aspects of learning. The analytic results are used to improve material, optimize content, and diversify instructional techniques. The findings of this study will help to improve digital-based English learning using PJBL, resulting in a more immersive and effective learning experience in higher education.